Can a paper-based device trace COVID-19 sources with wastewater-based epidemiology? - Mao, Kang; Zhang, Hua; Yang, Zhugen (American Chemical Society, 2020)
A recent outbreak of novel coronavirus pneumonia (COVID-19) caused by SARS-CoV-2 infection has spread rapidly around the globe, with cases now confirmed in 130 countries worldwide. Although public health authorities are racing to contain the spread of COVID-19 around the world, the situation is still grim. About 158 111 confirmed cases and 5946 cumulative deaths (81 059 confirmed cases and 3204 cumulative deaths from China) have been reported around the globe as of March 15, 2020. Some clinical cases have found that some carriers of the virus may be asymptomatic, with no fever, and no, or only slight symptoms of infection. Without the ability to screen these asymptomatic patients quickly and effectively, these unsuspecting carriers have the potential to increase the risk of disease transmission if no early effective quarantine measures are implemented. Therefore, to trace unknown COVID-19 sources, fast and accurate screening of potential virus carriers and diagnosis of asymptomatic patients is a crucial step for intervention and prevention at the early stage.
Keywords: Electrochemical detection; Infectious diseases; COVID-19; Fluorescence detection; Immunology